KERASULAN AWAM DAN TRANSFORMASI MASYARAKAT - Alexius Kurdo Irianto (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Reality of the Church today requires adaptation of the Church to the world situation. Moreover, the Church as the People of God should be relevant to the situation of its members. Coaching and teaching needs to be adapted to the situation and needs of the people, so that helped people live their faith in their appropriate background. Therefore, we need a catechesis which involves the situation and needs of the people. Catechesis appropriate to the situation and needs of the people is known as contextual catechesis. Catechesis of contextual context emphasizes the people